COMMUNICATION PATTERN OF KARAWANG ISLAMIC STUDENT FAMILY ORGANIZATION (KMIK) JAKARTA IN FORMING COHESIVE GROUPS - Afifah, Zahra Nur; Hermansah, Tantan; Nasichah (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2023)
Jabodetabek is a megapolitan area with a high rate of migrating students from all over Indonesia to continue their higher education. The Karawang Islamic Student Family (KMIK) Jakarta is a forum for Islamic students from Karawang who are in Jabodetabek to continue to work, accommodate aspirations, and serve the Karawang community. The wide scope of KMIK Jakarta requires an effective communication pattern that makes members wherever they are, will feel bound and belonging. The purpose of this study is to determine communication patterns and communication barriers that arise in the cohesive formation of the group. This study used descriptive qualitative approach and phenomenological research method. Data collection was done by interviews, and informant selection techniques by purposive sampling. The cohesive analysis of the group in this study used the Gorupthink Theory of Irvin L. Janis. Four indicators were obtained in this study, namely complex communication, effective communication, communication that is able to build enthusiasm, and high-intensity communication. Communication barriers that occur are differences in communication patterns in each management period. The existence of cohesive groups makes KMIK Jakarta able to face communication barriers that occur with star communication patterns or to all familial channels.